The personal utility of cfDNA screening: Pregnant patients' experiences with cfDNA screening and views on expanded cfDNA panels. Issue 1 (3rd November 2019) - Farrell, Ruth M.; Agatisa, Patricia K.; Michie, Marsha M.; Greene, Amy; Ford, Paul J.
Abstract: Prenatal cell‐free DNA screening (cfDNA) provides more genetic risk information about the fetus than has ever been possible. At the same time, the rapid expansion of new cfDNA panels raises important questions about how to structure patient‐centered discussions that best support patients' decision‐making about its use. To address this question, we conducted interviews with pregnant patients to identify decision‐making needs and preferences with respect to cfDNA in patient‐centered healthcare discussions, given its evolving capability to identify a range of fetal variants. Personal utility was a core concept guiding decision‐making. Participants spoke of how their deeply personal values and beliefs about maternal responsibility, actionability, and tolerance of uncertainty framed their view of the personal utility of cfDNA screening. While discussing their notions of personal utility with their healthcare provider, participants also had concerns about potential ramifications for the provider–patient relationship and shared decision‐making when disclosing values and preferences regarding disability, quality of life, and termination—particularly as it becomes possible to identify variants with different disease‐associated severity and outcomes. The complexities associated with the introduction of genomics in prenatal care present unique challenges to structuring effective shared decision‐making discussions between patients and their healthcare providers. While efforts are underway to determine how to best educate patients about the medical aspects of cfDNA, it is equally important to develop approaches in healthcare communication that enable patients to make informed, values‐based decisions about the use of cfDNA and its impact on their pregnancy.